Capturing the basics: the development of an expert computer system for physiotherapists. - Parry A; Stone S (Physiotherapy, 1991)
Can physiotherapists describe their core skills? How do they make clinical decisions? What are their sources of knowledge? What are the 'rules' of practice? These are some of the questions which are being addressed by the project described in this paper. Physiotherapists are utilising computerised systems to record their work for Korner purposes. This project turns to a more novel application of computers: the development of an expert system which can give students and newly qualified practitioners access to expert advice and may be seen as a means of sharpening expertise by experienced practitioners themselves. The paper outlines briefly what an expert system is and the kinds of situations in which it can be useful. This is then related to a core area of physiotherapy and the choice of electrotherapy as the initial area of study is explained. Historically, computer software development has failed to live up to expectations because the purpose for which it has been designed has been poorly defined. The researchers' attempt to define a good specification for a computer system by paying attention to the nature of physiotherapy knowledge is described; the methodology used for eliciting knowledge from practitioners is discussed; and there is some analysis of the knowledge base of electrotherapy drawn from the preliminary results. Finally, some of the ethical and practical problems of developing a computer system which tries to emulate how physiotherapists make decisions and solve problems are raised as the basis of further discussion.